Code Mixing Used In Daily Conversation By The Female Students Of Ma’had Al-Jami’ah - Alfian Alfian; dian mukhlisa (English Literature Department, Adab and Humanities Faculty, 2019)
The purpose of this study is to analyze the use of code mixing by the students at Ma`had Al-Jamiah. This case study was used by interviewing nine female students in Ma’had Al-Jami’ah of the State Islamic Islamic University of STS Jambi. Beside interview, observation was conducted , in three room. The data were analyzed by using thematic analysis. The findings indicated that the kind of code switching used by the female students are in the form of noun and adjective. Several reasons for using code mixing are Environmental factor, the regulation in Ma`had and lack of vocabularies.